Modelling Tetraselmis sp. growth-kinetics and optimizing bioactive-compound production through environmental conditions. (February 2018) - Dammak, Mouna; Hadrich, Bilel; Barkallah, Mohamed; Hentati, Faiez; Ben Hlima, Hajer; Pichon, Chantal; Denis, Michel; Fendri, Imen; Michaud, Philippe; Abdelkafi, Slim
Highlights: Four non-linear models were evaluated for predicting cell-growth kinetic. Baranyi-Roberts model was selected to assess the microalgae growth-kinetic values. The greatest content-values achieved for chlorophyll and carotenoid compounds. Combination of decreased salinity and light stress contributed to starch accumulation. Abstract: The aim of this study is to predict Tetraselmis cells growth-kinetic and to induce the synthesis of bioactive compounds (chlorophylls, carotenoids and starch) with high potential for biotechnological applications. Using the statistical criteria, the Baranyi-Roberts model has been selected to estimate the microalgae growth-kinetic values. The simultaneous effects of salinity, light intensity and pH of culture medium were investigated to maximize the production of total chlorophylls, carotenoids and starch. The optimal culture conditions for the production of these compounds were found using Box-Behnken Design. Results have shown that total chlorophyll and carotenoids were attained 21.6 mg·g −1 DW and 0.042 mg·g −1 DW, respectively. In addition, the highest starch content of 0.624 g·g −1 DW has been obtained at neutral pH with high irradiance (182 μmol photons m −2 s −1 ) and low salinity (20). A highly correlation (R 2 = 0.884) has been found between the gravimetric and flow cytometric measurements of chlorophyll content.